2019
DOI: 10.1111/nan.12568
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Pathology of pituitary neuroendocrine tumours: present status, modern diagnostic approach, controversies and future perspectives from a neuropathological and clinical standpoint

Abstract: E. Manojlovic-Gacic, J. Bollerslev, O. Casar-Borota (2020) Neuropathology and Applied Neurobiology 46, 89-110 Invited Review: Pathology of pituitary neuroendocrine tumours: present status, modern diagnostic approach, controversies and future perspectives from a neuropathological and clinical standpoint Neuroendocrine tumours of the adenohypophysis have traditionally been designated as pituitary adenomas to underline their usually indolent growth and lack of metastatic potential. However, they may demonstrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 152 publications
(208 reference statements)
3
15
0
Order By: Relevance
“…Although grading of symptoms was not possible in our study, the results imply persisting mental health issues despite achieved biochemical remission. The findings in study IV support two previous cross-sectional studies in which increased prevalence of psychopathology and cognitive impairment was found after remission for 11 (range 1-32), and 13 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years, respectively (90,91).…”
Section: Study IVsupporting
confidence: 88%
See 2 more Smart Citations
“…Although grading of symptoms was not possible in our study, the results imply persisting mental health issues despite achieved biochemical remission. The findings in study IV support two previous cross-sectional studies in which increased prevalence of psychopathology and cognitive impairment was found after remission for 11 (range 1-32), and 13 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years, respectively (90,91).…”
Section: Study IVsupporting
confidence: 88%
“…Most clinically non-functioning adenomas stain positive for gonadotropins, and on rare occasions for prolactin, ACTH or growth hormone, and are referred to as "silent" gonadotrophs, lactotrophs, corticotrophs and somatotrophs respectively. Less than 3% are immunonegative for all hormones/transcription factors and are termed null cell adenomas (5,6). Evaluation of proliferation markers, somatostatin receptors and granulation patterns may have prognostic and/or predictive implications.…”
Section: Tumours Of the Anterior Pituitary Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are concordant with a report that silent ACTH and gonadotroph tumors share cytopathological features and clinical behavior 29 . Taking into account that cell-specific methylation patterns are preserved during development and tumorigenesis, it is also possible that null cell, a subset of gonadotrophs and of corticotroph adenomas share a common precursor 30,31 10,32,33 (Figure 1B). In addition, a study showed that a subset of functioning corticotroph adenoma displayed a more intermediate methylation profile between FPT and NFPT 10,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that cell-specific methylation patterns are preserved during development and tumorigenesis, it is also possible that null cell, a subset of gonadotrophs and of corticotroph adenomas share a common precursor 30,31 10,32,33 (Figure 1B). In addition, a study showed that a subset of functioning corticotroph adenoma displayed a more intermediate methylation profile between FPT and NFPT 10,32,33 . Specific gene mutations such as GATA3 and USP8 accounted for the differences among these corticotroph adenomas variants 10,28 .…”
Section: Discussionmentioning
confidence: 99%